Analysing Quality Management Practices in After Sales Service Delivery in Ghana: Insights from Selected Heavy-Duty Machinery Companies in Tarkwa - Evans, Twumasi (University of Mines and Technology, Tarkwa. Ghana, 2024)
The study examines quality management (QM) practices after-sales service delivery from the perspective of selected engineering firms in Ghana. The study's four objectives were to: analyze the dimensions of QM practices; identify the QM practices required for efficient after-sales service delivery; investigate the direct effects of QM on competitive advantage; and investigate the impact of QM practice training on service delivery in the engineering firms that were chosen. In all, 72 management staff from Cummins Ghana Ltd, Mantrac Ghana Ltd, and Panafrican Equipment Group responded to the questionnaire. This study employs a descriptive research technique to give perspective and in-depth analysing of QM practices in after-sales service delivery. The findings showed that engineering businesses' top management was more committed to improving the quality of services delivered by making quality management choices, creating a culture of quality, and recognizing, motivating, and supporting staff members. The top management support helped the engineering firms meet customer wants, increase corporate confidence, and bring in more clients, sales, and repeat business. To enhance the QM practices after-sales service delivery in the selected engineering firms, the researcher recommends that employee involvement in decision-making, employee training, management support, and adopting strong leadership as well as focus on the customer must be enhanced. Finally, limitation for the study and future research were identified.
Keywords: Quality Management, sale delivery, employee training, leadership